Desarrollo de aplicación de escritorio para la gestión de historias clínicas de la clínica veterinaria de la Universidad Antonio Nariño sede Circunvalar. (2023)
The management of medical records in clinics or hospitals allows for the control of a patient's clinical information, and thus it impacts the healthcare services provided to users. While information management in human clinics and hospitals has seen significant advancements in recent years, thanks to information technologies, it is still an evolving field in veterinary clinics.